Degeneration of corticofugal fibers in a patient with primary progressive freezing gait: A case report. Issue 19 (May 2017) - Seo, Jeong Pyo; Chang, Min Cheol
Abstract: Rationale: To report a patient with primary progressive freezing gait (PPFG) whose degeneration of corticofugal tract (CFT) from the supplementary motor area (SMA) was demonstrated using diffusion tensor tractography (DTT). Patient concerns: A 66-year-old woman presented with a solitary symptom of a sudden transient break on walking (i.e., freezing gait), which slowly progressed for 4 years. Diagnoses: Imaging evidence using magnetic resonance imaging and 18 F-florinated-N-3-fluoropropyl-2-β-carboxymethoxy-3-β-(4-lodophenyl) nortropane positron emission tomography scanning was unremarkable, and our patient's symptom was not affected by dopamine agonist medication. Based on the clinical symptoms and imaging findings, we diagnosed our patient as having PPFG. Interventions: From the patient and 20 age- and sex- matched normal controls, diffusion tensor imaging data were acquired using a 1.5 T magnetic resonance scanner. Outcomes: In DTT findings, the CFT from the left SMA was partially torn and thinned. Moreover, the fractional anisotropy value and tract volume of CFT from the left SMA were more than two standard deviations lower than those of normal controls. Lessons: In our opinion, the lesion in the CFT from the left SMA in our patient was attributed to the occurrence of PPFG. We believe that the results of this study suggest one of the pathological mechanisms for the occurrence of gait difficulty in PPFG.